Caffeine Extraction from Spent Coffee Grounds by Solid-liquid and Ultrasound-assisted Extraction: Kinetic and Thermodynamic Study - Raheem, Salsabeel; Al-yaqoobi, Atheer; Znad, Hussein; Abid, Hussein Rasool (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Coffee is the most essential drink today, aside from water, the high consumption of coffee and the byproducts of its soluble industries such as spent coffee grounds can have a negative effect on the environment as a source of toxic organic compounds. Therefore, caffeine removal from the spent coffee ground can be applied as a method to limit the effect of its production on the environment. The aim of this study is to determine the kinetics and thermodynamics parameters and develop models for both processes based on the process parameters by using traditional solid-liquid extraction and Ultrasound-assisted extraction methods. The processes were performed at a temperature range of 25 to 55 °C for traditional and ultrasound baths, and experimental time ranged from 5- 60 min. The results demonstrated that under the above conditions, the extraction process applies to the pseudo-first-order reaction, where the rate constant K value increases with temperature. The transition state parameters were also discussed where these parameters indicated that the system of the process exhibited an activated complex formation state resulting in a thermodynamically unfavorable process, and the thermodynamic parameters at the equilibrium state were also evaluated in terms of the obtained yield percentage. The results also showed that the ultrasound-assisted bath process showed a spontaneous behavior at temperatures of 45 °C and 55 °C with D°G of -1192.9703 and - 2725.25 J/mole. On the other hand, for the traditional method, the extraction process was approaching a spontaneous behavior with the temperature increasing where at 25 °C the D°G value was 10379.944 J and at a temperature of 55 °C it reached 8004.26 J/mole.